The caldera-forming eruption of Ksudach volcano about cal. A.D. 240: the greatest explosive event of our era in Kamchatka, Russia - Braitseva O.A.; Melekestsev I.V.; Ponomareva V.V.; Kirianov V.Yu. (Journal of Volcanology and Geothermal Research, 1996)
The largest Plinian eruption of our era and the latest caldera-forming eruption in the Kuril-Kamchatka region occurred about cal. A.D. 240 from the Ksudach volcano. This catastrophic explosive eruption was similar in type and characteristics to the 1883 Krakatau event. The volume of material ejected was 18–19 km3 (8 km3 DRE), including 15 km3 of tephra fall and 3–4 km3 of pyroclastic flows. The estimated height of eruptive column is 22–30 km. A collapse caldera resulting from this eruption was 4 × 6.5 km in size with a cavity volume of 6.5–7 km3. Tephra fall was deposited to the north of the volcano and reached more than 1000 km. Pyroclastic flows accompanied by ash-cloud pyroclastic surges extended out to 20 km. The eruption was initially phreatomagmatic and then became rhythmic, with each pulse evolving from pumice falls to pyroclastic flows. Erupted products were dominantly rhyodacite throughout the eruption. During the post-caldera stage, when the Shtyubel cone started to form within the caldera, basaltic-andesite and andesite magma began to effuse. The trigger for the eruption may have been an intrusion of mafic magma into the rhyodacite reservoir. The eruption had substantial environmental impact and may have produced a large acidity peak in the Greenland ice sheet.